EgSeverin and Eg14-3-3zeta from Echinococcus granulosus are potential antigens for serological diagnosis of echinococcosis in dogs and sheep. (June 2023) - Zhang, Xiaoli; Wei, Chenxi; Lv, Yajie; Mi, Rongsheng; Guo, Baoping; Rahman, Sajid Ur; Zhang, Yehua; Cheng, Long; Jia, Haiyan; Huang, Yan; Han, Xiangan; Gong, Haiyan; et al.
Abstract: Cystic echinococcosis (CE) is a zoonotic parasitic disease caused by the metacestode larva of Echinococcus granulosus . In this study, two-dimensional gel electrophoresis (2-DE) coupled with immunoblot analysis revealed that E. granulosus severin and 14-3-3zeta proteins (named EgSeverin and Eg14-3-3zeta, respectively) might be two potential biomarkers for serological diagnosis of echinococcosis. The recombinant EgSeverin (rEgSeverin, 45 kDa) and Eg14-3-3zeta (rEg14-3-3zeta, 35 kDa) were administered subcutaneously to BALB/c mice to obtain polyclonal antibodies for immunofluorescence analyses (IFAs). And IFAs showed that both proteins were located on the surface of protoscoleces (PSCs). Western blotting showed that both proteins could react with sera from E. granulosus- infected sheep, dog, and mice. Indirect ELISAs (rEgSeverin- and rEg14-3-3zeta-iELISA) were developed, respectively, with sensitivities and specificities ranging from 83.33% to 100% and a coefficient of variation (CV %) of less than 10%. The rEgSeverin-iELISA showed cross-reaction with both E. granulosus and E. multilocularis, while the rEg14-3-3zeta-iELISA showed no cross-reaction with other sera except for the E. granulosus- infected ones. The field sheep sera from Xinjiang and Qinghai were analyzed using rEgSeverin-iELISA, rEg14-3-3zeta-iELISA, and a commercial kit respectively, and no significant differences were found among the three methods ( p > 0.05). However, the CE positive rates in sheep sera from Qinghai were significantly higher than those from Xinjiang ( p < 0.01). Overall, the results suggest that EgSeverin and Eg14-3-3zeta could be promising diagnostic antigens for E. granulosus infection. Highlights: Both EgSeverin and Eg14-3-3zeta were located on the surface of protoscoleces of E. granulosus . The rEgSeverin-iELISA could be used in the detection of anti- E. granulosus or anti- E. multilocularis sera. The rEg14-3-3zeta-iELISA could only be employed for the detection of anti- E. granulosus sera. It is the first time to develop the iELISAs based on two antigens-EgSeverin and Eg14-3-3zeta.